Description of the last-instar larva of Zenithoptera lanei Santos, 1941 (Odonata: Libellulidae) - Rippel, Camila Gisel (2020)
The larva of Zenithoptera lanei Santos, 1941 is described and illustrated based on three exuviae of reared larvae collected in Misiones, Argentina, Roraima and Amazonas, Brazil. A comparison with the larva of Z. anceps Pujol-Luz, 1993 is included.